Private ECUs: Unhappy triad - Peter Bofinger (Intereconomics, 1986)
The growing use of the European Currency Unit (ECU) in private transactions is often expected to produce a decisive impetus towards monetary integration within Europe. On the other hand, critics warn of the monetary risks of increased private use of the ECU. What are the opportunities and risks associated with the ECU? Is the importance of the ECU exaggerated at present?
Keywords: 330; European Monetary System